Wybrane zagadnienia prawa rolnego w Szwajcarii – obrót gruntami rolnymi, dzierżawa i finansowanie działalności rolniczej - Suchoń, Aneta (PRAWO i WIĘŹ, 2025)
The aim of this paper is to try to determine whether and to what extent selected agricultural legislation in Switzerland on issues such as the transfer of agricultural land, tenancy and agricultural financing takes into account the challenges of such aspects as running a stable agricultural business, protecting the environment and adapting to climate change. It is also worth considering which, if any, of the Swiss solutions to the above-mentioned issues could be used by the Polish legislator. The paper first focuses on agriculture and food security in the Swiss Constitution. Then, the Federal Law on Agriculture of 2 April 1998 is considered in more detail. This key Swiss agricultural legislation introduces instruments for the implementation of agricultural policy development. The paper then focuses on the Federal Law on the Right to Agricultural Land of 4 October 1991 (Bundesgesetz über das bäuerliche Bodenrecht), which imposes extensive restrictions on agricultural real estate transactions. The article also discusses the right of pre-emption of agricultural real estate, the inheritance of agricultural land and farms, the leasing of agricultural land, the financing of agricultural activities, and animal husbandry in Switzerland.